2016
DOI: 10.1016/j.celrep.2016.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer-Derived Lung Metastases Show Increased Pyruvate Carboxylase-Dependent Anaplerosis

Abstract: Cellular proliferation depends on refilling the tricarboxylic acid (TCA) cycle to support biomass production (anaplerosis). The two major anaplerotic pathways in cells are pyruvate conversion to oxaloacetate via pyruvate carboxylase (PC) and glutamine conversion to α-ketoglutarate. Cancers often show an organ-specific reliance on either pathway. However, it remains unknown whether they adapt their mode of anaplerosis when metastasizing to a distant organ. We measured PC-dependent anaplerosis in breast-cancer-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(205 citation statements)
references
References 38 publications
13
190
2
Order By: Relevance
“…Indeed, even simple approaches utilizing these principles have led to important insights [58, 59, 76]. More elegant models, albeit limited in experimental flexibility, have been important in pushing the boundaries of our understanding of tumor metabolism in vivo, illustrating the importance of context [4, 5, 810]. Future studies integrating these concepts and techniques will be critical to more clearly elucidate the metabolic role of the TME and associated therapeutic vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even simple approaches utilizing these principles have led to important insights [58, 59, 76]. More elegant models, albeit limited in experimental flexibility, have been important in pushing the boundaries of our understanding of tumor metabolism in vivo, illustrating the importance of context [4, 5, 810]. Future studies integrating these concepts and techniques will be critical to more clearly elucidate the metabolic role of the TME and associated therapeutic vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC), pyruvate carboxylase (PC) expression is upregulated in the primary tumors compared to normal tissues (Sellers et al, 2015). Increased PC-dependent anaplerosis has also been observed in growing lung metastases in vivo (Christen et al, 2016). In this study, it was shown that lung metastases upregulate PC expression and prefer utilizing pyruvate over glutamine to fuel the TCA, similar to what is observed in certain NSCLCs (Sellers et al, 2015).…”
Section: Lung Metastases: Coping With An Extreme Pro-oxidant Environmentmentioning
confidence: 99%
“…Although tumour cells can hijack nutrients from the cells they encounter as they arrive in an organ, nutrient availability might vary substantially between different organs. For instance, the availability of pyruvate in lungs activates pyruvate carboxylase (PC) in metastatic breast cancer cells, which in turn converts pyruvate to oxaloacetate, thereby enhancing anaplerosis (Box 1) (Christen et al, 2016). Additional studies carried out on in vitro three-dimensional (3D) models have revealed that breast cancer cells rely on the non-essential amino acid proline, through proline dehydrogenase enzyme (PRODH) activity, to form spheroids in vitro and lung metastases in vivo (Elia et al, 2017).…”
Section: Fuelling Metastatic Progressionmentioning
confidence: 99%